PENGARUH MOTIVASI KEPALA BADAN TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI BADAN PUSAT STATISTIK KABUPATEN CIREBON - Atik Sridani Wismayanti; Nurudin Siraj; Sri Wulandari (Jurnal Ilmiah Publika, 2016)
ABSTRACT The research that the writer did was the Effect of Motivation by the Head of the Agency on Employee Productivity at the Cirebon Regency Central Statistics Agency. The research method that I do is a quantitative research method, which starts with data collection, data interpretation, until the results of the research use numbers.The problem that the author pointed out is that the work productivity of employees at the Cirebon Regency Central Bureau of Statistics has not been maximized, it is suspected that the problem is caused by the lack of optimal motivation implementation by the head of the Cirebon Regency Central Statistics Agency.The research question that the writer proposes is the influence of motivation by the head of the body on employee work productivity. The hypothesis that the authors propose is as follows: "It is suspected that there is a positive and significant influence between the motivation of the head of the agency on the work productivity of employees at the Cirebon Central Statistics Agency."From this hypothesis a statistical hypothesis can be formulated, namely: H0 (Zero Hypothesis): rs count <from rs table, then the formulation of the problem is: "There is no positive and significant influence between the motivation of the head of the agency on employee work productivity at the Cirebon Regency Statistics Agency. "and Ha (Alternative hypothesis): rs count> rs table, then the formulation of the problem is:" There are a positive influence and significant correlation between motivation by the head of the agency to work productivity of employees at the Central Bureau of Statistics of Cirebon."In the study showed that the results the motivation made by the head of the Cirebon Regency Central Bureau of Statistics was good enough, but it was not optimal as seen from the successful implementation of motivation which reached 60.6% with a total score of 1637, and employee work productivity was good enough but not optimal as reaching 59.5% with a total score of 1740.The implementation of motivation by the head of the agency has a close influence on the work productivity of employees at the Cirebon Central Statistics Agency with a value of rs calculated 0.805 and when compared with rs table with a 5% precision of 0.248. Because the RS calculated is greater than rs table, there is a positive and significant influence between the motivation of the head of the agency on the work productivity of employees at the Cirebon Central Statistics Agency. Thus H0 (Zero Hypothesis) is rejected and Ha (Alternative Hypothesis) is accepted.